Impact of Customer Behavior on Impulse Buying in the Footwear Industry - Parditha, I Putu; Mahyuni, Luh Putu (PT Mattawang Mediatama Solution, 2025)
This study examines the influence of brand image, content marketing, influencer marketing, and customer reviews on impulsive buying behavior in the context of New Balance footwear in Indonesia. The research aims to understand the interplay of these factors and their impact on spontaneous purchasing decisions. Data were collected from respondents through surveys, focusing on demographic attributes, consumer preferences, and purchasing behavior. The analysis utilized a structured model to evaluate the relationships between variables and their influence on impulsive buying. The findings reveal that while relevant to consumer perceptions, brand image and content marketing do not significantly drive impulsive purchases. Conversely, influencer marketing demonstrates a substantial positive impact, emphasizing its role in creating emotional connections and triggering spontaneous buying. Customer reviews, however, show limited moderating influence on the relationships between the studied variables and impulsive buying behavior. The study concludes that emotionally driven strategies, such as leveraging credible influencers and situational promotions, are more effective in fostering impulsive purchases than traditional approaches. It highlights the need for creative and dynamic marketing tactics to align with evolving consumer behavior. This research contributes to understanding consumer behavior in the digital marketing landscape. It offers actionable insights for businesses to optimize strategies and enhance customer engagement, ensuring sustainable success in competitive markets.